2021
DOI: 10.48550/arxiv.2102.04631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability for an inverse source problem of the biharmonic operator

Abstract: In this paper, we study for the first time the stability of the inverse source problem for the biharmonic operator with a compactly supported potential in R 3 . Firstly, to connect the boundary data with the unknown source, we shall consider an eigenvalue problem for the bi-Schr: odinger operator ∆ 2 `V pxq on a ball which contains the support of the potential V . We prove a Weyl-type law for the upper bounds of spherical normal derivatives of both the eigenfunctions φ and their Laplacian ∆φ corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Proof. The uniqueness can be proved similarly to the deterministic case given in [21]. It then suffices to show the existence and regularity of the solution.…”
Section: The Direct Problemmentioning
confidence: 94%
See 1 more Smart Citation
“…Proof. The uniqueness can be proved similarly to the deterministic case given in [21]. It then suffices to show the existence and regularity of the solution.…”
Section: The Direct Problemmentioning
confidence: 94%
“…The reason is not only the increase of the order which leads to the failure of the methods developed for the second order equations, but also the properties of the solutions for the higher order equations are more sophisticated. Some of the inverse boundary value problems for bi-and poly-harmonic operators can be found in [8,12,13,21,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The first stability result was obtained in [4] for the inverse source problem of the Helmholtz equation by using multi-frequency data. Later on, the increasing stability was studied for the inverse source problems of various wave equations including the acoustic, elastic, and electromagnetic wave equations, as well as the wave equation with the biharmonic Schrödinger operator [5,12,17,18,[22][23][24]. A more recent study on the stability for the inverse medium problem can be found in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by [22,24], we consider an eigenvalue problem for the Schrödinger operator in Ω and deduce integral equations, which connect the scattering data u(x, κ)| Γ and the unknown source function f . It is required to obtain a bound of the analytic continuation of the data from the given data to the higher frequency data in order to show the stability.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is concerned with the inverse source problem of determining f from the boundary measurements upx, kq, ∇upx, kq, ∆upx, kq, ∇∆upx, kq, x P BB R corresponding to the wavenumber k given in a finite interval. In general, there is no uniqueness for the inverse source problems of the wave equations at a fixed frequency [2,12]. Computationally, a more serious issue is the lack of stability, i.e., a small variation of the data might lead to a huge error in the reconstruction.…”
Section: Introductionmentioning
confidence: 99%